Analysis and prediction of nutritional outcome of patients with pediatric inflammatory bowel disease from Bahrain - Hasan M. Isa; Masooma Mohamed; Ahmed Alsaei; Zahra Isa; Enjy Khedr; Afaf Mohamed; Haitham Jahrami (BMC, 2024)
Abstract Background Inflammatory bowel disease (IBD) is a chronic gastrointestinal disease that causes anorexia, malabsorption, and increased energy requirements. Childhood IBD can significantly impact nutritional status and future health. Objective This study aimed to analyze the nutritional status of patients with pediatric IBD at presentation and during follow-up and to identify predictors of nutritional outcome. Methods This retrospective cohort study reviewed the medical records of children diagnosed with IBD in the Pediatric Department, Salmaniya Medical Complex, Bahrain, 1984 − 2023. Demographic data, clinical characteristics, and anthropometric data were collected. World Health Organization growth standards were used to interpret nutritional status. Results Of the 165 patients, 99 (60%) had anthropometric data at presentation, and 130 (78.8%) had follow-up data. Most patients were males (64.6%) and had Crohn's disease (CD) (56.2%), while 43.8% had ulcerative colitis (UC). The median age at presentation was 10.9 years and the mean follow-up duration was 12.6 years. At presentation, 53.5% of the patients were malnourished, that decreased to 46.9% on follow-up. Thinness was reduced from 27.3% at presentation to 12.1% at follow-up (p = 0.003). There was an increased tendency to normal weight on follow-up (59.6%) compared to time of presentation (46.5%), p = 0.035. Overweightness showed a non-significant increase from 26.3% at presentation to 28.3% at follow-up (p = 0.791). Children with IBD were more likely to become obese when they grow up to adulthood (2.3% versus 20.5%, respectively, p < 0.001). Weight-for-age, and height-for-age at presentation were higher among CD compared to UC, but body mass index (BMI) at follow-up was higher among UC patients (p < 0.05). Thinness at follow up was associated with very early-onset disease (p = 0.02), lower weight and BMI at presentation (p < 0.001 each), younger age at follow-up (p = 0.002), pediatric age group (p = 0.023), lower hematocrit (p = 0.017), and higher C-reactive protein (p = 0.007). Overweight at follow up was associated with increased weight and BMI at presentation (p < 0.001 each), longer disease duration (p = 0.005), older age (p = 0.002), and azathioprine intake (p = 0.026). Considering follow-up duration, univariate analysis exhibited that Bahraini nationality, post-diagnosis disease duration, age at follow-up, occurrence of diarrhea, height, and BMI at presentation were factors that decreased liability to abnormal nutritional status, while CD, history of weight loss, perianal disease, and skin rash, and intake of prednisolone expressed increased liability of abnormal nutritional status (p < 0.05). Conclusion Pediatric IBD is associated with a high incidence of malnutrition. Thinness is more prominent at presentation, while overweight is higher on follow-up. Multiple risk factors aggravating abnormal nutritional status were highlighted. Accordingly, nutritional counseling should be prioritized in a multidisciplinary approach.